Probabilidade de ocorrência de dias trabalháveis com tratores agrícolas em Uberaba, Minas Gerais - Vieira de Assis, Simone; C Sediyama, Gilberto; Leite Vianello, Rubens; Martyn, Peter John (Revista Ceres, 2025)
The soil moisture balance for Uberaba, MG, was calculated using daily rainfall data, daily actual evapotranspiration data and total soil water availability. The number of working days and the computed probabilities of having good or bad working days for agricultural tractors were both obtained from the upper limit value of soil water availability and three precipitation values of 0.2, 5,0, 10.0 mm.